2024
DOI: 10.1111/resp.14679
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound is a promising screening tool to rule out interstitial lung disease in patients with rheumatoid arthritis

M. Otaola,
F. Paulin,
M. Rosemffet
et al.

Abstract: Background and ObjectiveIt is still controversial how to screen for interstitial lung disease (ILD) in patients with rheumatoid arthritis (RA). We aimed to evaluate the performance of lung ultrasound (LUS) as a screening tool for RA‐ILD and to compare it with the performance of chest auscultation, chest x‐ray and pulmonary function tests (PFTs).MethodsCross‐sectional study of consecutive RA patients evaluated at a Rheumatology Clinic in Buenos Aires between January and December 2022. High‐resolution computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Our cross-sectional study found parenchymal abnormalities in LUS in almost half of low symptomatic RA patients, similar to two recent studies by Santos Moreno and Otaola et al that described the narrow base reverberation (B lines) in a high percentage in RA-ILD [33,49], also in the early phase of disease [33].…”
Section: Discussionsupporting
confidence: 92%
“…Our cross-sectional study found parenchymal abnormalities in LUS in almost half of low symptomatic RA patients, similar to two recent studies by Santos Moreno and Otaola et al that described the narrow base reverberation (B lines) in a high percentage in RA-ILD [33,49], also in the early phase of disease [33].…”
Section: Discussionsupporting
confidence: 92%